Relational inclusivity in education: comparing SNA Toolkit findings with ERGM models to advance a relational approach to inclusion - Mallén-Lacambra, Carlos; Mamas, Christoforos (Frontiers in Education, 2025)
IntroductionInclusion is a universal right and a fundamental pillar of education. However, current educational models often overlook the relational nature of students, failing to address this social challenge effectively. Relational inclusivity emphasizes the importance of interpersonal relationships in fostering equitable and inclusive learning environments. The SNA Toolkit is a practical and versatile software that enables educators to assess student relationships through Social Network Analysis (SNA), promoting relational inclusivity. While widely recognized for its accessibility and versatility, its data quality has not been systematically compared with advanced statistical techniques, such as Exponential Random Graph Models (ERGMs). This study aimed to evaluate the consistency of the SNA Toolkit by comparing its findings with ERGMs, assessing its accuracy in providing high-quality actionable insights for educators.MethodsUsing a cross-sectional observational design, the study analyzed 32 7th-grade students from a socio-demographically diverse classroom in California. A peer-nomination survey mapped the four key networks of relational inclusivity: friendship, recess, academic support, and emotional wellbeing. Data were analyzed using both the SNA Toolkit and ERGMs to examine network structures, homophily, and relational dynamics.ResultsResults revealed that the SNA Toolkit closely aligned with ERGM outputs, confirming its consistency. Across the four networks, both analyses indicated low density (< 0.22; β < 1.82) and high reciprocity (>0.52; β > 1.82). Homophily effects for gender, SEND and ethno-racial group were also consistent, with E–I Index ranging from −0.05 to −0.39 below expected, and β = 0.311–1.327. By contrast, no evidence of socioeconomic status homophily was found.DiscussionWhile ERGMs provided inferential insights, the SNA Toolkit effectively captured the same patterns through descriptive and visual analyses, making it more accessible for educators. These findings position the SNA Toolkit as a practical, evidence-based tool for fostering relational inclusivity, allowing educators and researchers to identify isolated students, assess group cohesion, and implement targeted interventions to create more inclusive learning environments.